Low incidence of pneumocystis pneumonia utilizing PCR‐based diagnosis in patients with B‐cell lymphoma receiving rituximab‐containing combination chemotherapy. Issue 11 (22nd August 2016) - Barreto, Jason N.; Ice, Lauren L.; Thompson, Carrie A.; Tosh, Pritish K.; Osmon, Douglas R.; Dierkhising, Ross A.; Plevak, Matthew F.; Limper, Andrew H.
Abstract : Recent literature has demonstrated concern over the risk of Pneumocystis jirovecii pneumonia (PJP) when administering rituximab with combination chemotherapy such as in R‐CHOP; however, the exact risk and potential need for prophylaxis is unknown. We sought to determine the incidence of PJP infection following R‐CHOP administration in patients with B‐cell lymphoma. Consecutive patients diagnosed with B‐cell lymphoma receiving R‐CHOP were evaluated from chemotherapy initiation until 180 days after the last administration. The primary outcome was cumulative incidence of PJP infection. Secondary endpoints included the association of rituximab, prednisone and subsequent chemotherapy with PJP infection risk. A total of 689 patients (53% male, median age 66 years) were included. Seventy‐three percent of patients completed at least 6 cycles of R‐CHOP treatment. Median rituximab and prednisone cumulative doses were 3950 mg and 5325 mg, respectively. Median daily prednisone dose through end of treatment was 45 mg (range 7.6 mg to 119 mg). The cumulative incidence of PJP was 1.51% (95% CI 0.57–2.43, at maximum follow‐up of 330 days), below 3.5%, the conventional threshold for prophylaxis. Univariate analysis did not detect a statistically significant association between PJP and rituximab, steroids, or receipt of additional chemotherapy in this patient population. Our results demonstrate a low occurrence of Pneumocystis pneumonia during R‐CHOP treatment of B‐cell lymphoma and argue against universal anti‐ Pneumocystis prophylaxis in this setting. Further investigations should focus on targeted anti‐ Pneumocystis prophylaxis for patients presenting with high‐risk baseline characteristics or when receiving rituximab‐inclusive intensive combination chemotherapy regimens as treatment for other aggressive lymphoma subtypes. Am. J. Hematol. 91:1113–1117, 2016. © 2016 Wiley Periodicals, Inc.